Meter in traditional Kakataibo chants - Prieto Mendoza, Alejandro Augusto (2021)
This paper studies the principal aspects of meter of three traditional Kakataibo chants (a Panoan group of Peruvian Amazonia). Regarding meter, Kakataibo chants exhibit patterns relevant for the cross-linguistic study of line and meter typology. I describe the Kakataibo system of versification as a quantitative meter that counts an exact number of moras and regulates the distribution of these by imposing grouping restrictions; also, it establishes weight differences between light, heavy and superheavy syllables, and vowel lengthening plays an important role for meter purposes. In addition, the average duration of lines tends to last less than three seconds and decreases progressively during performance.